Cryo-synthesized Prussian blue analogues as advanced cathode materials for potassium-ion batteries - Qu Zhongli; Luo Wendi; Gao Caitian; Liu Yanfang; Shi Zude; Rao Apparao M.; Li Feifan; Lu Bingan (National Science Open)
Prussian blue analogues (PBAs) are increasingly recognized as promising cathode materials for potassium-ion batteries (PIBs) owing to their low cost, distinctive open structure, and high theoretical capacity. However, PBAs still face challenges related to low crystallinity and elevated crystal water content, adversely affecting their performance as cathodes. This study proposes a straightforward low-temperature synthesis method for PBAs termed cryo-synthesized PBAs. The nucleation and growth processes were effectively slowed down by precisely controlling the synthesis temperature. This approach successfully yields PBAs with enhanced crystallinity and uniform particle size. The PBA electrode utilized as the cathode in PIBs demonstrates remarkable long-term cycling stability over 10,000 cycles at a current density of 2000 mA g−1. We believe these findings will promote the widespread adoption of PBAs in aqueous PIBs, paving the way for large-scale, cost-effective applications.